Machine‐learning‐based virtual screening to repurpose drugs for treatment of Candida albicans infection. Issue 8 (19th June 2022) - Gao, Andrew; Kouznetsova, Valentina L.; Tsigelny, Igor F.
Abstract: Background: Approximately 30% of Candida genus isolates are resistant to all currently available antifungal drugs and it is highly important to develop new treatments. Additionally, many current drugs are toxic and cause unwanted side effects. 1, 3‐beta‐glucan synthase is an essential enzyme that builds the cell walls of Candida . Objectives: Targeting CaFKS1, a subunit of the synthase, could be used to fight Candida . Methods: In the present study, a machine‐learning model based on chemical descriptors was trained to recognise drugs that inhibit CaFKS1. The model attained 96.72% accuracy for classifying between active and inactive drug compounds. Descriptors for FDA‐approved and other drugs were calculated, and the model was used to predict the potential activity of these drugs against CaFKS1. Results: Several drugs, including goserelin and icatibant, were detected as active with high confidence. Many of the drugs, interestingly, were gonadotrophin‐releasing hormone (GnRH) antagonists or agonists. A literature search found that five of the predicted drugs inhibit Candida experimentally. Conclusions: This study yields promising drugs to be repurposed to combat Candida albicans infection. Future steps include testing the drugs on fungal cells in vitro.